Pattern of Relationship between Motivation and Job Performance Effectiveness of Truck Drivers in Logistics Industry: the Application of Canonical Correlation: แบบแผนความสัมพันธ์ระหว่างแรงจูงใจและประสิทธิผลการปฏิบัติงานของ พนักงานขับรถบรรทุกในอุตสาหกรรมโลจิสติกส์: การประยุกต์ใช้สหสัมพันธ์คาโนนิคอล - Dhiratanuttdilok, Tanutpats; Pasunon, Prasopchai (Journal of Applied Economics and Management Strategy, 2021)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ (1) ศึกษาระดับความสัมพันธ์ของแรงจูงใจและประสิทธิผลการปฏิบัติงานของพนักงานขับรถบรรทุกในอุตสาหกรรมโลจิสติกส์ และ (2) เพื่อศึกษาแบบแผนความสัมพันธ์ของแรงจูงใจและประสิทธิผลการปฏิบัติงานของพนักงานขับรถบรรทุกในอุตสาหกรรมโลจิสติกส์ กลุ่มตัวอย่างที่ใช้ในการศึกษาคือ พนักงานขับรถบรรทุกที่ถือใบอนุญาตขับรถประเภทที่ 3 (ท.3) และประเภทที่ 4 (ท.4) ในเขตพื้นที่ภาคตะวันออกของประเทศไทยจำนวน 402 คน งานวิจัยนี้ใช้การสุ่มตัวอย่างแบบอย่างง่ายและวิเคราะห์ข้อมูลโดยใช้เทคนิคการวิเคราะห์สหสัมพันธ์คาโนนิคอล ผลการศึกษา พบว่า ระดับความสัมพันธ์ของแรงจูงใจและประสิทธิผลการปฏิบัติงานของพนักงานขับรถบรรทุกที่มีระดับสูงทั้งหมด 11 คู่ ส่วนแบบแผนความสัมพันธ์ คือ ฟังก์ชั่นคาร์โนนิคอลที่ 1 แรงจูงใจ มีความสัมพันธ์กับประสิทธิผลการปฏิบัติงานที่สหสัมพันธ์คาโนนิคอลเท่ากับ 0.71 อย่างมีระดับนัยสำคัญ 0.01 และสามารถอธิบายความสัมพันธ์ดังกล่าวได้ร้อยละ 51 ทั้งนี้ แรงจูงใจค่ามีค่าน้ำหนักความสำคัญคาโนนิคอลระหว่าง 0.520-0.895 และประสิทธิผลการปฏิบัติงานของพนักงานขับรถบรรทุกมีค่าน้ำหนักความสำคัญคาโนนิคอลระหว่าง 0.762-0.946 อย่างไรก็ตาม ผลการวิจัยนี้เพื่อให้ผู้ประกอบการขนส่งสามารถใช้เป็นแนวทางในการพัฒนาพนักงานขับรถบรรทุกให้มีประสิทธิภาพต่อไป ABSTRACT The purposes of this research are (1) to study the levels of the relationship between the motivation and job performance effectiveness of truck drivers in the logistics industry; and (2) to study the patterns of the relationship between the motivation and job performance effectiveness of truck drivers in the logistics industry. The sample size of this research is 402 truck drivers that held a truck driving license Type 3 and Type 4 in eastern Thailand. This research used simple sampling and analysis was carried out using the canonical correlation technique. The study indicates that there are 11 relationships among the motivation and job performance effectiveness of truck drivers, which are related at high level. The pattern of the relationship is only canonical function no.1. This means that the relationship between motivation and job performance effectiveness is at 0.7, with the statistically significant difference at 0.01. Moreover, the canonical function no.1 can describe the relationship between the motivation and job performance effectiveness of truck drivers at 51 percent. The canonical loading of motivation is 0.520-0.895, and the canonical loading of job performance effectiveness is 0.762-0.946. Additionally, the results of this research can be useful for transport business owners as a guide to improving truck drivers’ efficiency.